The Education of Aqidah and Akhlaq in the Family of K.H. Hanafie Gobit - Firdaus, Nehna Puteri; Huda, Nuril (The Future of Education Journal, 2025)
This research, titled “The Education of Aqidah and Akhlaq in the Family of K.H. Hanafie Gobit,” examines how aqidah and moral education are applied within the family of a prominent Islamic educator from South Kalimantan. The research is motivated by growing concerns over the moral decline of younger generations in the face of globalization and technological advancement, highlighting the crucial role of family education as the primary foundation in shaping children’s character. The family of K.H. Hanafie Gobit is selected because it is widely recognized for successfully raising children with strong aqidah and noble character. The study aims to describe the implementation of aqidah and akhlaq education in this family. Using a qualitative approach with a biographical study design, data were collected through interviews and documentation. The subjects of the study are the children of K.H. Hanafie Gobit, while the focus of investigation is the family’s educational practices. The findings reveal that aqidah education is carried out through advice, habituation, exemplary behavior, and storytelling, with core materials including belief in Allah, His Books, His Messengers, the Day of Judgment, and Divine Decree. Moral education is delivered through similar methods, advice, habituation, and role modelling and covers personal morals, family ethics, social conduct, and religious behavior. The study concludes that parental roles are highly influential in shaping children’s personalities. Consistent and affectionate transmission of Islamic values has a significant impact on character formation. The educational model practiced by K.H. Hanafie Gobit offers a valuable reference for strengthening Islamic character education in the modern era.